2015
DOI: 10.3103/s074792391503010x
|View full text |Cite
|
Sign up to set email alerts
|

An Approach to the short- and long-term forecasting of strong earthquakes: A case study of the M w = 9.0 Tohoku earthquake, Japan, March 11, 2011

Abstract: Seismic hazard forecasts submitted in real time mode to the Kamchatkan Branch of the Russian Expert Council (KB REC) on Earthquake Prediction, Seismic Hazard, and Risk Assessment are described. In the first long term forecasts (September 7 and November 9, 2009), based on the GLOBAS_place tech nique (GLOBal Activation of Seismicity), we forecasted the occurrence of earthquakes with M ≥ 6.6 in the region of 35° N-40° N (Japan) and in three other regions of the world. In the forecasts submitted on Febru ary 25, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…Others claim that the Earth's interior was originally hydrogen-rich (Shcherbakov and Kozlova, 1986;Toulhoat and Zgonnik, 2022) or that there are significant H2 concentrations in the core (Isaev et al, 2007). Serpentinization of iron-rich rocks may be a major secondary source of natural hydrogen (Gaucher, 2020;Boreham et al, 2021), and multiple occurrences of hydrogen have been documented near faults where they have also been used for earthquake prediction (Wakita et al, 1980;Ware et al, 1984;Satake et al, 1984;Sato et al, 1984, Arai et al, 2008Fongliang and Gui-ru (1981); Sugisaki et al, 1983;Rogozhin et al, 2010;Shirokov et al, 2015;Jones and Pirkle, 1981). Wakita et al (1980) reported up to 3% hydrogen by volume along the Yamasaki fault in southwestern Japan, and Sugisaki et al (1983) reported up to 9.36% hydrogen along other active faults in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…Others claim that the Earth's interior was originally hydrogen-rich (Shcherbakov and Kozlova, 1986;Toulhoat and Zgonnik, 2022) or that there are significant H2 concentrations in the core (Isaev et al, 2007). Serpentinization of iron-rich rocks may be a major secondary source of natural hydrogen (Gaucher, 2020;Boreham et al, 2021), and multiple occurrences of hydrogen have been documented near faults where they have also been used for earthquake prediction (Wakita et al, 1980;Ware et al, 1984;Satake et al, 1984;Sato et al, 1984, Arai et al, 2008Fongliang and Gui-ru (1981); Sugisaki et al, 1983;Rogozhin et al, 2010;Shirokov et al, 2015;Jones and Pirkle, 1981). Wakita et al (1980) reported up to 3% hydrogen by volume along the Yamasaki fault in southwestern Japan, and Sugisaki et al (1983) reported up to 9.36% hydrogen along other active faults in Japan.…”
Section: Introductionmentioning
confidence: 99%